THE ROLE OF ORGANIZATIONAL BEHAVIOR IN ENHANCING THE PERFORMANCE OF FACULTY MEMBERS: AN ANALYTICAL STUDY OF THE OPINIONS OF A SAMPLE OF FACULTY MEMBERS AT THE COLLEGE OF ADMINISTRATION AND ECONOMICS / UNIVERSITY OF BAGHDAD - Adnan Rasheed Awad; Mosa Hamad Mohamad; Abdalfatah Hassan (Scholar Express Journals, 2024)
The research aims to understand the role of organizational behavior in improving the performance of faculty members at the College of Administration and Economics, University of Baghdad. The research relied on a questionnaire as the main tool for collecting the necessary data to achieve its objective. A total of (88) questionnaires were distributed to the faculty members of the college (research sample), and (83) were retrieved. The study used a comprehensive survey method for all the data. The researcher designed the questionnaire based on scientific sources and previous studies. The most significant findings revealed a statistically significant effect of organizational behavior on the performance of the faculty members at the College of Administration and Economics, University of Baghdad. Additionally, a set of statistical methods were used, including the arithmetic mean, standard deviation, simple correlation coefficient, and multiple regression to test the research hypotheses.
Keywords: Organizational behavior - Technology – Performance